The design, development and analysis of a hybrid household refrigerator combining thermoelectric and vapour compression cooling systems - Söylemez, Engin (My University, 2018)
TERMOELEKTRİK VE BUHAR SIKIŞTIRMALI SOĞUTMA SİSTEMLERİNDEN OLUŞAN HİBRİD EV TİPİ BUZDOLABININ DİZAYNI, GELİŞTİRİLMESİ VE ANALİZİTermoelektrik (TE) ve buhar sıkıştırmalı soğutma sistemlerinden oluşan hibrit ev tipi buzdolapları deneysel ve nümerik olarak incelenmiştir. Bunun için, ticari olarak uygun termoelektrik soğutucular ticari buzdoplarının taze gıda ve chill bölmelerine uygulanmıştır. Analizler termoelektrik soğutma teknolojilerinin uygulama fırsatlarını arttırmak için termoelektrik soğutucuların faydalarına odaklanmıştır. Bu çalışmanın iki aşaması bulunmaktadır. İlk aşamada, çalışmanın amaçları belirlenmiş ve takip eden hazırlıklar yapıldı: termoelektrik soğutucuların belirlenmesi için 0 °C(chill) ve taze gıda bölmeleri için soğutma yükü hesapları yapılmıştır. Daha sonra, iki referans (seri) ev tipi buzdolabının yanı sıra iki de farklı hibrit ev tipi buzdolabı üretilmiş ve deneysel olarak incelenmiştir. Daha fazla değerlendirme için, bilgisayar destekli akışkan dinamiği analizi (CFD) verileri için gerekli ölçümler yapılmıştır. İkinci safhada ise, en iyi test sonuçlarına sahip hibrit ev tipi buzdolabı sonraki değerlendirmeler için seçilmiştir. Hibrit buzdolabının nümerik analizleri sonrası, CFD modeli geliştirilmiş ve bu modelle önerilen konfigürasyonların analizleri de yapılmıştır. CFD analizinin amacı daha düzgün hava akış ve sıcaklık dağılımı elde etmede termoelektrik soğutucu için en uygun yeri belirlemektir. CFD tahminleri dikkate alınarak, en az sıcaklıktabakalaşmasına sahip konfigürasyon temel alınarak iki yeni hibrit buzdolabı yapılmıştır. CFD tahminleri test sonuçlarıyla daha sonra teyit edilmiştir.Bu çalışmanın sonucu önemli çıktılar içermektedir. Enerji tüketiminin azaltılmasında sağlanan iyileştirmelere rağmen, hibrit buzdolaplarının enerji tüketimi, seri buzdolaplarına kıyasla hala üç kat daha yüksektir. Bu, termoelektrik soğutma teknolojisinin, ölçümlerin işaret ettiği gibi, buhar sıkıştırmalı teknolojiye alternatif olması için Performans Katsayısı’nda (COP) iyileştirmelere ihtiyaç duyduğunu vurgular. Termoelektrik soğutucuların COP'si testlerde 0.3 ila 0.5 W/ W arasındaydı. Alternatif olabilmesi için, termoelektrik soğutucuların COP değerleri yaklaşık 2 W/ W olmalıdır.Bununla birlikte, hibrit ev tipi buzdolapları, soğutma kapasitesi testlerinde kanıtlandığı üzere, sıcak gıdaların soğutulmasını hızlandırmak açısından muazzam bir potansiyele sahiptir. Yani, sıcak gıda maddeleri, gıdaların güvenli bir şekilde korunabileceği hedef sıcaklık bölgelerine kadar dakikalar içinde soğutulabilir. Ayrıca, buzdolaplarının bölmesinde çok düzgün sıcaklık dağılımı ve daha az sıcaklık dalgalanmaları termoelektrik soğutucular tarafından sağlanabilir. Bu, sıcaklık farklılıklarına çok duyarlı olan bozulmaya karşı hassas gıdaların bozulmadan daha uzun bir süre tutulması için çok önemlidir. TE teknolojisindeki gelişmeler ve yenilikler önemli ölçüde artmaktadır ve bu nedenle TE soğutma teknolojilerinin verimliliği artacaktır. Bu durum ev tipi buzdolaplarına uygulanan buhar sıkıştırmalı soğutma teknolojisine güçlü bir alternatif olmalarına yardımcı olacaktır. Bu kesinlikle biraz zaman alacak olsa da, ev tipi buzdolaplarında son kullanıcıların bazı özel ihtiyaçları için TE soğutucuları kullanmak mümkün olacaktır.

THE DESIGN, DEVELOPMENT AND ANALYSIS OF A HYBRID HOUSEHOLD REFRIGERATOR COMBINING THERMOELECTRIC AND VAPOUR COMPRESSION COOLING SYSTEMSHybrid household refrigerators which combine vapour compression (VC) and thermoelectric (TE) cooling technologies were experimentally and numerically investigated. In order to realise this investigation, commercially available thermoelectric coolers (TEC) were applied to the fresh food (FFC) and chill (CC) compartments ofcommercial refrigerators. Analysis focused on the benefits of TECs to increase opportunities for the application of the thermoelectric cooling technologies. There were two phases of this work. In the first phase, the objectives of the work were set, and the following preparations were made: the reference refrigerators were selected and the target compartments, CC and FFC, for the implementation of the TECs were determined. The cooling loads for them were calculated to determine the suitable TECs. Another necessary test equipment was also collected. Then, two different hybrid household refrigerators were built along with two reference household refrigerators(serial refrigerators) and they were investigated experimentally. For further evaluations, necessary measurements were made to collect data for Computational Fluid Dynamics (CFD) analysis. In the second phase, the hybrid household refrigerator (HHR) with better test results was selected for further evaluations. After numerical analysis of hybrid refrigerator, CFD model was developed and then proposed configurations were also analysed. The purpose of the CFD analysis was to determine the optimum location for the TEC to achieve more uniform air flow and temperature fields. Regarding the predictions, two new hybrid refrigerators were built based on the configurations which have less temperature stratification. CFD predictions were validated with the experimental results, later on. The conclusion of this work has pivotal outputs as follows. Although enhancements achieved in reducing energy consumption, HHRs’ energy consumption is still three times higher compared to serial refrigerators. This highlights that TE cooling technology needs improvements in Coefficient of Performance (COP) to become an alternative to VC technology as measurements indicated. The COP of TECs were between 0.3 to 0.5 W/ W. To become an alternative, TEC’s COP values must be around 2 W/ W. Nevertheless, HHRs have an enormous potential in terms of speeding up the warm foodstuffs’ cooling as proved in cooling capacity tests. That is, the warm foodstuffs can be cooled down in minutes to the target temperature regions in where foods can be safely preserved. Moreover, highly uniform temperature distribution and less temperature fluctuations in the compartment of the refrigerators can be provided by the TECs. This is crucial for keeping the perishable foods, which are very sensible to temperature differences, for a longer time without deterioration.The developments and innovations in TE technology are significantly increasing and therefore the efficiency of TE cooling technologies will likely increase which help them to be a strong alternative to VC cooling technology applied to household refrigerators. Although this will certainly take some time, it will possible to use TECs for somespecific needs of end-users in household refrigerators.
Keywords: Buhar Sıkıştırmalı Thermoelectric; Cooler; Makine mühendisliği; Mechanical engineering; Refrigeration and refrigerating machinery; Soğutma ve soğutma makineleri; Soğutucu; Termoelektrik; Termoelektrik soğutma; Thermoelectric cooling; Thermoelectricity; Vapour Compression